"Water Sensitive City" Within City as A Strategy for Activate Polluted Urban Areas. Issue 10 (February 2019) - Januszkiewicz, Krystyna; Golebieski, Jakub
Abstract: The paper deals with the possibilities of urban and architectural design to benefit human condition, which encompasses physical well-being, environmental quality of life in big cities during the Climate Change era. Cities are dependent on the ecosystems beyond the city limits, but also benefit from internal urban ecosystems. This paper focuses on issues relevant for urban areas, the attention is on direct and locally generated services relevant for Szczecin. The first part of the paper depicts what the term "water sensitive city" means in urban design as a way to encapsulate a fuzzy concepts of an ideal relationship between people, governance, built environment, infrastructure, living ecosystems, resource use (e.g. energy) and water. This section also includes the example of project North Harbour, Northern Europe's largest new urban development area in Copenhagen where this concept is implemented. The second part of the paper presents the results of the research for the Łasztownia Island in Szczecin by Jakub Golebiewski and Tomasz Sachanowicz team (West Pomeranian University of Technology in Szczecin). Currently, the Łasztownia Island remains as a degraded and polluted area in Szczecin's inner city. In conclusion, the paper emphasizes the implementation the concept "water sensitive city" is the desired strategy for reactivation this urban area. This also allows the ecosystems close to the city centre to be linked with larger ecosystems outside of the city.